NEW DISTRIBUTIONAL RECORDS OF INDODYNERUS CAPITATUS GUSENLEITNER, 2008 (HYMENOPTERA : VESPIDAE : EUMENINAE) - KUMAR, P. GIRISH; KISHORE, LAMBERT; SHAREEF, K.P. MOHAMMED (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2013)
The species lndodynerus capitatus Gusenleitner, 2008 is recorded for the first time from Chhattisgarh and Kerala.